THE SEARCH FOR INDIVIDUAL IDENTITY IN SHERIDAN'SAUGUST RUSH MOVIE: PSYCHOLOGICAL APPROACH - KURNIAWATI, ARSITA DYAH SEPTIANA (2011)
This study aims at showing the search for individual identity in August Rush movie by using psychological approach. The objectives of this study are analyzing the movie based on its structural elements and analyzing the movie based on the psychological approach. This research is qualitative research. The types of data of the study are text and image taken from two data sources: primary and secondary. The primary data source is the August Rush movie directed by Kristen Sheridan released in 2007. While the secondary data sources are other materials taken from books, journals, articles, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise-en-scene, cinematography, sound, and editing are related to each other and form a good unity of movie. Second, based on the psychological analysis, it suggests that personal trait helps one find his or her individual identity.